2017
DOI: 10.1128/mspheredirect.00190-17
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Generation and Characterization of New Zika Virus Isolate Using Sequence Data from a Microcephaly Case

Abstract: The major complications of an ongoing Zika virus outbreak in the Americas and Asia are congenital defects caused by the virus’s ability to cross the placenta and infect the fetal brain. The ability to generate molecular tools to analyze viral isolates from the current outbreak is essential for furthering our understanding of how these viruses cause congenital defects. The majority of existing viral isolates and infectious cDNA clones generated from them have undergone various numbers of passages in cell cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
96
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(102 citation statements)
references
References 49 publications
4
96
0
2
Order By: Relevance
“…Previous studies with Asian isolates showed reduced replication kinetics and peak virus titers in vitro, mosquito infection and dissemination rates, reduced virulence in various murine knockout models, tissue distribution, virus replication, weight loss, clinical disease when compared with African isolates. [43][44][45][46][47][48][49][50][51] To further examine these differences, we examined the virulence of the PRVABC59 isolate from Puerto Rico in the IFN-I antibody blockade mouse model. Similar to the results obtained with the CPC-0740 isolate, infection produced no clinical disease or lethality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with Asian isolates showed reduced replication kinetics and peak virus titers in vitro, mosquito infection and dissemination rates, reduced virulence in various murine knockout models, tissue distribution, virus replication, weight loss, clinical disease when compared with African isolates. [43][44][45][46][47][48][49][50][51] To further examine these differences, we examined the virulence of the PRVABC59 isolate from Puerto Rico in the IFN-I antibody blockade mouse model. Similar to the results obtained with the CPC-0740 isolate, infection produced no clinical disease or lethality.…”
Section: Discussionmentioning
confidence: 99%
“…A huge effort has been made in the last few years to overcome the instability problems associated with ZIKV infectious cDNA clones, and several approaches have been successfully implemented 18 , including the in vitro ligation of cDNA fragments 24,25 , low-copy plasmids 19,20 , the inactivation of cryptic bacterial promoters by the introduction of silent mutations 26,27 , intron insertion 21,22,23 , the Gibson assembly method 30 , the ISA method 28,29 , and the use of CPER 31 . Although these approaches overcome the toxicity problem and are useful to generate ZIKV infectious cDNA clones, some of them are laborious and present several disadvantages, including the need for in vitro ligation and transcription steps that reduce virus recovery efficiency or the introduction of a high number of silent mutations to inactivate cryptic bacterial promoter that could affect viral fitness, among others.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this toxicity problem, several nontraditional approaches have been implemented successfully in the last two years 18 . These include the use of low-copy-number plasmids 19,20 , the insertion of introns to disrupt the toxic regions 21,22,23 , the in vitro ligation of cDNA fragments 24,25 , mutational silencing of cryptic bacterial promoters present in the viral genome 26,27 , infectious subgenomic amplicons (ISA) 28,29 , the Gibson assembly method 30 , and the use of circular polymerase extension reaction (CPER) 31 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study we challenged detector cell lines with ZIKV of African (MR766) and Asian lineages (PE243) during 14and 28-day in vitro assays to assess standard GMP guidelines for adventitious virus testing. We report that the general in vitro adventitious virus test with a CPE end point, as used in GMP-compliant safety testing of biologicals, was [41,54,55] where African strains showed a higher infection rate than Asian strains, and varying yields of virus produced in human neuronal cell lines were recently reported. In the context of quality assurance and GMP compliance it is therefore also important to assess whether strains from different origins are robustly detectable, and the variation in susceptibility of detector cell lines must be taken into account when assessing the presence of ZIKV in biologicals.…”
Section: Discussionmentioning
confidence: 99%